2016
DOI: 10.1175/jas-d-16-0106.1
|View full text |Cite
|
Sign up to set email alerts
|

Diurnal Variations of the Land–Sea Breeze and Its Related Precipitation over South China

Abstract: Convection-permitting numerical experiments using the Weather Research and Forecasting (WRF) Model are performed to examine the diurnal cycles of land and sea breeze and its related precipitation over the south China coastal region during the mei-yu season. The focus of the analyses is a 10-day simulation initialized with the average of the 0000 UTC gridded global analyses during the 2007–09 mei-yu seasons (11 May–24 June) with diurnally varying cyclic lateral boundary conditions. Despite differences in the ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
104
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 119 publications
(116 citation statements)
references
References 63 publications
6
104
0
Order By: Relevance
“…Although land–sea breeze could be an essential mechanism that controls the diurnal variation of coastal rainfall in south China (Chen et al, , ), the precipitation over the two stages in this event was probably not dominated by land–sea breeze. The land–sea breeze and associated diurnal cycle of precipitation were relatively weak (not shown) due to high southerly wind (Chen et al, ; Wang & Sobel, ).…”
Section: Resultsmentioning
confidence: 99%
“…Although land–sea breeze could be an essential mechanism that controls the diurnal variation of coastal rainfall in south China (Chen et al, , ), the precipitation over the two stages in this event was probably not dominated by land–sea breeze. The land–sea breeze and associated diurnal cycle of precipitation were relatively weak (not shown) due to high southerly wind (Chen et al, ; Wang & Sobel, ).…”
Section: Resultsmentioning
confidence: 99%
“…Another sensitivity experiment NOVAP was performed similarly to the IDEAL experiment except that the evaporation of liquid water, which prevents the cold pool generation from moisture convection process, was turned off. A similar methodology has been used to study diurnal cycles of precipitation in many different regions (Trier et al, 2010;Sun and Zhang, 2012;Bao and Zhang, 2013;Chen et al, 2016Chen et al, , 2017. The biggest advantage of this method is that it is able to capture the general characteristics of the diurnal cycle of precipitation and the related dynamical processes instead of just focusing on a single case.…”
Section: Observation Dataset and Methodologymentioning
confidence: 99%
“…Interactions between land breeze and prevailing wind are likely to produce precipitation over the coastal area or tropical islands (Keenan et al, 1988;Chen et al, 2017). Recent studies (Bao et al, 2013;Chen et al, 2016Chen et al, , 2017 have also found that convectively driven cold pools and latent cooling, as well as environmental wind and moisture, may play important roles in the propagation and maintenance of diurnal rainfall in coastal regions. How cold pools and latent cooling affect the diurnal cycle of rainfall and related LSB over a tropical island has not been studied extensively.…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies have suggested that diurnal cycles of rainfall and convection over South China exhibit pronounced regional and intraseasonal variations (G. Chen et al, ; X. Chen, Zhao, et al, ; X. Chen et al, ; Jiang et al, ). Morning rainfall is dominant over offshore regions because of the surface convergence between the northerly land breeze and the prevailing southerly low‐level monsoonal wind (G. Chen et al, ; X. Chen et al, ; X. Chen et al, ). The rainfall and convection over the inland northeastern mountainous area exhibits two diurnal peaks.…”
Section: Introductionmentioning
confidence: 99%
“…Chen et al, 2015;Jiang et al, 2017). Morning rainfall is dominant over offshore regions because of the surface convergence between the northerly land breeze and the prevailing southerly low-level monsoonal wind (G. Chen et al, 2018;X. Chen et al, 2016;X.…”
Section: Introductionmentioning
confidence: 99%